2000
DOI: 10.1177/1420326x0000900308
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Area and Personal Airborne Asbestos Samples during Abatement in a Crawl Space

Abstract: Air sample data were collected during asbestos abate ment of two buildings using area and personal sampling methods. Abatement involved removal of pipe insula tion from crawl spaces. The two sampling methods were compared to determine if there was a relationship be tween them. A relationship was observed between area and personal airborne samples in building 2 as deter mined by correlation and regression but is most likely due to chance. One major outlier was detected for both area and personal measurement sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…Although it is true that these controls also provide information for protection to the environment and public (public health) [5]. Previous studies have suggested that occupational exposure (personal) sampling and area sampling are not related [21,31,33,[35][36][37][38][39][40][41][42][43] and provide statistically different exposure concentrations [21,33,35]. Comparison studies have further shown that personal (occupational) measurements are often statistically greater in concentration than area samples [21,33,35].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although it is true that these controls also provide information for protection to the environment and public (public health) [5]. Previous studies have suggested that occupational exposure (personal) sampling and area sampling are not related [21,31,33,[35][36][37][38][39][40][41][42][43] and provide statistically different exposure concentrations [21,33,35]. Comparison studies have further shown that personal (occupational) measurements are often statistically greater in concentration than area samples [21,33,35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that occupational exposure (personal) sampling and area sampling are not related [21,31,33,[35][36][37][38][39][40][41][42][43] and provide statistically different exposure concentrations [21,33,35]. Comparison studies have further shown that personal (occupational) measurements are often statistically greater in concentration than area samples [21,33,35]. Since the purpose of engineering/ work practice controls is for occupation exposure protection [4,33], the best measure of this effectiveness is personal sampling [4,12,19,21,41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations